Predictors of blood pressure response: Obesity is associated with a less pronounced treatment response after renal denervation. Issue 1 (23rd June 2015) - Id, Dani; Bertog, Stefan C.; Ziegler, Ann‐Kathrin; Hornung, Marius; Hofmann, Ilona; Vaskelyte, Laura; Matic, Predrag; Gafoor, Sameer; Sievert, Horst
Abstract : Objectives: The purpose of this study was to identify predictors of BP response. Background: Catheter‐based renal denervation (RDN) causes significant blood pressure (BP) reductions in a large number of patients with resistant hypertension. Methods: One hundred one consecutive patients with resistant hypertension who underwent RDN with the Symplicity™ catheter were included in this retrospective study. Primary endpoint was the change in office systolic BP after 6 months. Uni‐ and multivariate logistic regression analyses were performed to detect baseline predictors of a significant BP response 6 months after RDN (age, gender, office and ambulatory BP, renal function, body mass index [BMI], diabetes mellitus, antihypertensive medication, number of ablations). Results: The procedure was technically uneventful in all patients. Mean BP at baseline was 166.6/90.2 ± 22.5/16.4 mmHg and decreased by −14.7 ( P  < 0.0001)/−5.3 ( P  < 0.001) ± 22.8/14.1 mm Hg at 6‐month follow‐up. Similarly, paired analysis of 24‐hr‐ambulatory BP measurement ( n  = 71) showed a significant reduction of mean systolic BP by 6.8 ± 14.4 mm Hg ( P  < 0.0002). Upon univariate analyses, a higher baseline office systolic BP ( P  < 0.0001) and lower BMI ( P  = 0.014) were identified as significant predictors of the magnitude of BP response after 6 months. Importantly, on multivariate analysis, baseline office systolic BP (standardized ß  = −0.46; r  = −0.47; P  < 0.0001) and BMI (standardized ß  = 0.21; r  = 0.95; P  = 0.019) remained significant. Conclusion: Blood pressure reductions after RDN were more pronounced in patients with higher baseline blood pressure and lower BMI. These findings may have implications regarding patient selection for renal denervation. © 2015 Wiley Periodicals, Inc.